Journalism that Matters: Views from Central and Eastern Europe. By Michał Głowacki, Epp Lauk and Auksė Balčytienė. Bern: Peter Lang, 2014, 214 pp.; ISBN: 978-3-631-65421-7 hb. - Rodina, Elena (2015)
This book is a much-needed contribution to journalistic studies that allows us to have a closer and more nuanced look at media systems and press cultures in the countries of Central and Eastern Europe (CEE) from a non-Western perspective. The volume is of high value to anyone who is interested in the diversity that underlies the unifying term of “post-communist media.” Most of its authors rely on rich data collected throughout lengthy periods of time on the territory of Central and Eastern Europe, which allows us to see not only the current state of “Eastern” media, but its development throughout time.